Arthur$1 (Bs eyess - Brown, Marc Tolon (Boston : Little, Brown, 1979)
His friends tease Arthur when he gets glasses, but he soon learns to wear them with pride.
"An Atlantic-Monthly Press book."
Keywords: Eyeglasses -- Fiction; Animals -- Fiction